Sociodemographic and medical risk factors associated with antepartum depression - Babu, Giridhara R.; Murthy, Gudlavalleti Venkata Satyanarayana; Singh, Neeru; Nath, Anita; Rathnaiah, Mohanbabu; Saldanha, Nolita; Deepa, R.; Kinra, Sanjay (Frontiers Media, 2018)
Background: The increasing recognition of antenatal depression is an emerging area of concern in developing countres. We conducted a study to estimate the prevalence of antenatal mental distress and its relation with sociodemographic factors, obstetric factors, and physiological wellbeing in pregnant women attending public health facilities in Bengaluru, South India. Methods: Nested within a cohort study, we assessed the mental status in 823 pregnant women in two public referral hospitals. Kessler Psychological Distress Scale (K-10 scale) was used to assess maternal depression. We collected information related to social-demographic characteristics and recent medical complaints. Descriptive statistics and odds ratios were calculated using SPSS version 20. Results: Results show that 8.7% of the women exhibited symptoms of antenatal depression. Sociodemographic characteristics, such as respondent occupation, husband education, husband’s occupation, total family income showed significance. First time pregnancy, anemia, and high blood pressure were also associated with mental distress. Conclusion: Our study has demonstrated feasibility of screening for mental health problems in public hospitals. Early detection of mental distress during pregnancy is crucial as it has a direct impact on the fetus. The public health facilities in low- and middle-income countries such as India should consider piloting and scaling up screening services for mental health conditions for pregnant women.